Havasupai NT14 (eHRAF World Cultures, 2011)
The Havasupai collection covers a wide range of ethnographic data, covering a time period from approximately 1776 to 2004. Two of the major ethnographies on the traditional culture of the Havasupai are Spier and Cushing. These are supplemented by Smithson who compares modern (twentieth century) Havasupai ethnography to what it was like before European contact, and Schwartz whose culture summary, although relatively brief, covers a wide range of topics. The document by Smithson and Euler provides information on religion and mythology. Land rights and inheritance are topics discussed in Service and Martin. Other subjects of interest in this collection are: prehistory in Schwartz; political structure and leadership in Martin; diet in Bonyshek, and Martin who describes three distinct versions of Havasupai-Hualapai origins and ethnohistoric relations as suggested by Kroeber, Schwartz, and Euler and Dobyns